New tool to assess the force production in the swallow - Bango, B.; Sillero Quintana, M.; Grande, I. (Science of Gymnastics Journal, 2013)
8 men artistic gymnasts were evaluated with a new test protocol in order to assess isometric strength in an specific hold position on still rings. The proposed test protocol measures the force applied the gymnast on the rings from an initial lying prone position on a force platform while he is trying to achieve the Swallow (or Hirondelle) position. The vertical force (FZ) from the forcetime curve registered (100 Hz) was used and it showed a descent from the initial body weight level caused by the gymnast force on the rings and, later, a maximal isometric force period. Fundamental and derivate variables to extract from the evolution of Fz were defined. Results showed significant statistical differences between gymnasts that could perform the Swallow (P) from those that could not (NP) (p<0.05). Performer gymnasts were characterized by a higher percentage of body weight descent and higher strength in relation to body mass (p<0.05). The practical application of this tool could be to provide coaches with information about how close the gymnast is to perform the Swallow.